2011
DOI: 10.1007/s00248-011-9936-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Associated with the Intestinal Tract of P. monodon in Commercial Farms

Abstract: The potentially important roles of intestinal bacteria on immune response, disease resistance, and nutrition for the black tiger shrimp Penaeus monodon have been increasingly investigated. However, so far, little is known about the intestinal bacterial community of the shrimp in the commercial aquaculture settings. In this study, the intestinal bacterial communities of juvenile P. monodon (70 individuals) from eight commercial farms in Thailand were examined using 16S rDNA PCR-DGGE, and seven 16S rDNA clone li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
69
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 63 publications
11
69
0
2
Order By: Relevance
“…In our study, most of the OTUs identified by SSCP gels treated with the probiotics belong to phylogenic groups class -and-proteobacteria, flavobacteria, shingobacteria, and fusobacteria, compared with other species of invertebrates, where the microbiota were represented by class -, -, and -proteobacteria in fleshy prawn Fenneropenaeus chinensis (Lui et al, 2011),by fusobacteria and -proteobacteria in giant tiger prawn Penaeus monodon (Chaiyapechara et al, 2011), and by derribacteres, mollicutes, -and -proteobacteria, small fractions of firmicutes, cytophaga-flavobacter-bacteroides, verricomicrobiae, -andproteobacteria in vent shrimp (Durand et al, 2010).Furthermore, the gut content of shrimps inoculated with the Bacillus mix and Alibio had higher bacterial diversity, compared with the controls, supported by the total number of OTU´s. The intestinal bacterial community shows a similar dominance of -proteobacteria and flavobacteria at all times in shrimp treated with probiotics.…”
Section: Probiotics In Larvae and Juvenile Whiteleg Shrimp Litopenaeumentioning
confidence: 62%
See 1 more Smart Citation
“…In our study, most of the OTUs identified by SSCP gels treated with the probiotics belong to phylogenic groups class -and-proteobacteria, flavobacteria, shingobacteria, and fusobacteria, compared with other species of invertebrates, where the microbiota were represented by class -, -, and -proteobacteria in fleshy prawn Fenneropenaeus chinensis (Lui et al, 2011),by fusobacteria and -proteobacteria in giant tiger prawn Penaeus monodon (Chaiyapechara et al, 2011), and by derribacteres, mollicutes, -and -proteobacteria, small fractions of firmicutes, cytophaga-flavobacter-bacteroides, verricomicrobiae, -andproteobacteria in vent shrimp (Durand et al, 2010).Furthermore, the gut content of shrimps inoculated with the Bacillus mix and Alibio had higher bacterial diversity, compared with the controls, supported by the total number of OTU´s. The intestinal bacterial community shows a similar dominance of -proteobacteria and flavobacteria at all times in shrimp treated with probiotics.…”
Section: Probiotics In Larvae and Juvenile Whiteleg Shrimp Litopenaeumentioning
confidence: 62%
“…The resident community included Maribius salinus and Donghicola eburneus (-proteobacteria) and Wandonia haliotis (flavobacteria) in all treatments. Dominance of -proteobacteria occurs in the intestinal community of other crustaceans, including Fenneropenaeus chinensis (Liu et al, 2011), ornate rock lobster Panulirus ornatus (Payne et al, 2007), Rimicaris exoculata (Durand et al, 2009), European lobster Homarus gammarus L. (Daniels et al, 2010), and Penaeus monodon (Chaiyapechara et al, 2011).…”
Section: Probiotics In Larvae and Juvenile Whiteleg Shrimp Litopenaeumentioning
confidence: 99%
“…A previous study has reported that 90–95% of the bacterial phylotypes in the intestine of E. sinensis were Proteobacteria and Bacteroidetes, and that Bacteroidetes were common to all crab types (Li et al, 2007). For example, the phyla Proteobacteria, Bacteroidetes, and Firmicutes were most abundant in the digestive system of the black tiger shrimp P. monodon (Shakibazadeh et al, 2009; Chaiyapechara et al, 2012). Similarly, bacteria belonging to the Bacteroidetes phylum were more plentiful in the hepatopancreas, whereas those of the Firmicutes phylum were more plentiful in the foregut and intestine of the shrimp N. denticulate (Cheung et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…clone library analysis and denaturing gradient gel electrophoresis (DGGE), intestinal bacterial communities have been examined in various crustaceans, including the black tiger shrimp Penaeus monodon (Shakibazadeh et al 2009;Chaiyapechara et al 2012), red-tailed shrimp Penaeus penicillatus , Chinese shrimp Penaeus chinensis (Liu et al 2011), Atlantic blue crab Callinectes sapidus (Givens et al 2013), the cladoceran Daphnia magna (Freese and Schink 2011), and the copepod Eudiaptomus gracilis (Homonnay et al 2012). Advancement of nextgeneration sequencing (NGS) platforms has also facilitated more in-depth investigations into the gut microbiota of P. monodon (Rungrassamee et al 2013), the white shrimp Penaeus vannamei Huang et al 2015), and Norvegian lobster Nephrops norvegicus (Meziti and Kormas 2013).…”
Section: Introductionmentioning
confidence: 99%